Long-term Follow-up of Cytologically Indeterminate Thyroid Nodules Found Benign on Molecular Testing: A Validation Study - Michelle K. White MD; William B. Thedinger; Jagdish K. Dhingra MD (OTO Open, 2022)
Objective Molecular testing has revolutionized management of indeterminate thyroid nodules (Bethesda categories III and IV). Few studies have attempted to validate the negative predictive value of molecular tests. Using long-term observation as a surrogate for surgical resection, we sought to examine the false-negative rate of “benign” indeterminate thyroid nodules on molecular testing. Study Design Case series with retrospective data collection and chart review. Setting Large community-based practice with multiple satellite offices. Methods All patients with thyroid nodules that underwent ultrasound-guided fine-needle aspiration biopsy between 2013 and 2019 were evaluated through retrospective analysis. Cytologically indeterminate nodules reflexively underwent molecular testing to guide clinical management. Observation was recommended for lesions with benign molecular testing, and these nodules were followed clinically and by ultrasound. Results A total of 2011 nodules underwent fine-needle aspiration, of which 280 (14%) were indeterminate thyroid nodules. Of those 280 nodules, 100 (36%) were benign on molecular testing. Three samples were excluded from analysis due to patient deaths from unrelated causes. Surgical resection was recommended in 16 of the 97 nodules (17%), with the majority due to size and compressive symptoms. Histopathology was available in 14 nodules that underwent surgery, with 1 demonstrating minimally invasive follicular carcinoma. Conclusion While molecular testing is safe to use in guiding management of indeterminate thyroid nodules, consideration of individualized clinical factors and close long-term follow-up remains paramount.